Synthetic peptides corresponding to protective epitopes of Escherichia coli digalactoside-binding pilin prevent infection in a murine pyelonephritis model. - Schmidt, M A (Proc Natl Acad Sci U S A, 1988)
Synthetic peptides corresponding to five segments of a globoside (Gal-Gal)-binding pilin sequence [residues 5-12 (R5-12), R65-75, R93-104, R103-116, and R131-143], cyanogen bromide fragment II (CNBr-II, R53-163), and purified, intact Gal-Gal pili were prepared as vaccines and tested for their efficacy in a BALB/c murine model of pyelonephritis. Intact Gal-Gal pili, CNBr-II, and synthetic peptides R5-12 and R65-75 engendered antibodies that bound the homologous pilin protein and prevented urine and renal colonization in most vaccine recipients. Protection correlated with serum anti-pilus IgG ELISA titers greater than or equal to 1:250. The efficacy afforded by synthetic peptides R5-12 and R65-75 in vaccinated mice indicates that linear "antigenic" determinants in separate cyanogen bromide fragments encode "protective" epitopes. Peptides R93-104, R103-116, and R131-143 lacked efficacy, indicating that not all regions of the sequence are serologically equivalent. The crossreactivity of the peptide antisera for different Gal-Gal pilins was also assessed and correlated with the sequence homology of the corresponding regions. Antiserum to peptide R65-75, which corresponds to a region of unconserved sequence in heterologous pilins, bound only the homologous pilin. Thus, it specifies a type-specific protective epitope. Antiserum to synthetic peptide R5-12, which corresponds to a region of conserved sequence, bound Gal-Gal pilins from seven of eight pyelonephritis strains, indicating that it specifies a crossreacting protective epitope. IMAGES: